2020
DOI: 10.1111/acel.13231
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related differences in the translational landscape of mammalian oocytes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 54 publications
(104 reference statements)
3
19
0
Order By: Relevance
“…This could suggest that abnormal protein levels of chromosomal factors in aged oocytes might trigger compensatory mechanisms including increased polyadenylation of those transcripts for further translation. In support of this hypothesis, a recent study profiling the translatome of ageing mouse oocytes identified transcripts related to meiotic spindle formation and chromosome alignment as misregulated during translation (del Llano et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This could suggest that abnormal protein levels of chromosomal factors in aged oocytes might trigger compensatory mechanisms including increased polyadenylation of those transcripts for further translation. In support of this hypothesis, a recent study profiling the translatome of ageing mouse oocytes identified transcripts related to meiotic spindle formation and chromosome alignment as misregulated during translation (del Llano et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…shown that altered translation of specific transcripts is a contributing factor to the age-related quality decline in mouse oocytes (del Llano et al, 2020). Further studies will be needed to assess the role of CPEB2 in human oocytes.…”
Section: Transcripts Affected By Age Are Related To Oxidative Stress Mitochondrial Function Chromosome Segregation and Rna Metabolism Patmentioning
confidence: 99%
“…Whether or not these transcripts are similarly translated during reproductive aging remains to be determined. Recent work in mice has shown that reproductive aging in oocytes is associated with increased ribosome synthesis (Duncan et al 2017) and altered mRNA translation (Llano et al 2020). It is conceivable that human reproductive aging follows similar aging-related dysregulation, in which there is enhancement of the established mRNA decay programs.…”
Section: Gc Content Reveals Differential Correlations Between Mrna Hamentioning
confidence: 99%
“…4d, ⍴ = 0.39, p < 0.05).The correlation between the PACC and the reproductive aging CSC suggest that a subset of mRNA could be potentially stabilized and translated over a longer period of time during oocyte maturation. This phenomenon is called over-translation and has been observed in mice models for defects in translational mRNA decay (Sha et al 2018) as well as reproductively aged oocytes (Llano et al 2020).…”
Section: Age Associated Changes In Codon Optimalitymentioning
confidence: 99%
See 1 more Smart Citation